Business ethics: The changing face of working life - Yılmaz, Neslihan (IGI Global, 2023)
Ethics is about the behaviors that people enact on a social scale and that have consequences affecting others and the thinking processes that shape them. Business life is a part of social life and it has to develop principles compatible with value judgments in society. Increasing professional corruption is a situation where there is a complexity of values within the society and utilitarianism overcomes everything over time, and an ethical process is required. This can only be achieved through effective leadership.
Keywords: Working Life; Business Ethics; Changing